Exploratory calcineurin inhibitor-free regimens in living-related kidney transplant recipients - Garcia,R. (2007)
Chronic allograft nephropathy is among the major causes of graft loss even in low-risk kidney transplant recipients and correlates with acute nephrotoxic events during the first year post-transplant. Therefore, calcineurin inhibitor-free regimens may improve patient and graft survival among recipients of living-related kidney transplants. To confirm this hypothesis, we evaluated the efficacy and safety of two calcineurin inhibitor-free regimens in 92 low-risk recipients of one-haplotype living-related kidney transplants. Immunosuppression consisted of tacrolimus, azathioprine and prednisone (group I, GI, N = 38), 2 doses of daclizumab, mycophenolate mofetil (MMF), and prednisone (GII, N = 33) and 2 doses of daclizumab, MMF, sirolimus and prednisone (GIII, N = 21). At 12 months, treatment failure (biopsy-confirmed acute rejection, graft loss or death) was higher in GII compared to GIII and GI (54.5 vs 24.0 vs 13.1%, P < 0.01, respectively). In patients of black ethnicity the incidence of acute rejection was 25 vs 83.3 vs 20% (P = 0.055), respectively. Patient and graft survival was comparable. There were no differences in mean creatinine or calculated creatinine clearance at 12 months. Overall incidence of post-transplant diabetes mellitus (3.3%) and cytomegalovirus disease (4.3%) was similar in all groups. Further development of effective calcineurin inhibitor-free regimens should exclude patients of black ethnicity and may need full-induction therapy, perhaps with depleting agents, and concentration-controlled use of sirolimus and MMF.